Development of Problem-Based Learning Video Using Renderforest Application on Pythagoras Material - Ravilla, Trisca Dwi (Universitas Ahmad Dahlan, 2024)
This study explores the significant role of animated videos in enhancing students' learning motivation, grounded in the principles of motivational elements. Animated videos capture and sustain attention through visual appeal, engaging storytelling, interactivity, and emotionally engaging content. These elements make learning more relatable and enjoyable, leading to increased motivation and retention. Cognitive Load Theory posits that learners have a limited capacity for processing information, and animated videos can effectively manage the cognitive load by segmenting information, utilizing dual coding, and providing visual cues to guide attention. The successful development of a video-based learning medium on the Pythagorean theorem for eighth-grade students, created using the Renderforest application, demonstrates the practical application and potential of animated videos in education. The study suggests further development of such media into comprehensive, interactive applications to enhance students' learning motivation and understanding, highlighting the transformative potential of animation in educational settings.